The Dynamics of Lesbian Crime Fiction - Ramón Torrijos, María del (Estudios Ingleses de la Universidad Complutense, 2012)
Lesbian detective fiction offers a fundamental challenge to the accepted conventions of detection genre by firstly placing a female character in a traditional male role and secondly allowing her to transgress the conservative heterosexual norms of sexuality and identity. This paper aims to explore the formula of lesbian detection describing how writers such as Barbara Wilson, Mary Wings or Katherine V. Forrest through the creation of their lesbian detectives deal with the transformations applied to the detection genre when they manage to reconcile two apparently contradictory discourses: the detection genre, which assumes a masculine perspective of existence, and feminist thought which attempts to expand the rigid sexual stereotypes. Among the modifications operated in the genre, most of the texts avoid final resolution, reverse the traditional characterization of criminal and victim and are less concerned with the solving of a crime than with offering a subversive social critique revealing sexist practices. In this sense lesbian crime fiction deals with concerns and conflicts which are particularly relevant to women and forces the reader to confront their own feelings on questions concerning female power and social oppression, while challenging the existing structures of law and patriarchal authority.